Perbandingan Keterampilan Intrapersonal dan Interpersonal Berbasis Pendidikan Karakter Siswa Sekolah Dasar Negeri Kasihan Bantul - Akif Khilmiyah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
Students’ achievement can be shaped by three types of ability (capacity); academic, vocational and generic (personal ability). It appears that generic ability has predomi- nantly determined students’ achieve- ment, and therefore providing nurturing personal abaility is necessary. The objectives of this research are twofold: to study both intra and interpersonal skills of the students; to study similarities and differences the level of intra- and inter- personal skills of the students based on their sex, parent’s occupation, the level of class, and the order number of children in the family. The research was carried out in State Basic School of Kasihan, Bantul. The subjects of this research are 79 students in the grade IV, V, VI. This reserach concludes that there are 8 types of intrapersonal skills: self-awareness, self- confidence, effort to handle self-weak- ness, responsibilities, openness, assertiveness, self dicision making, effort to hadle stressful, and courage to express personal feelings. The lowest ability is self-confidence, and the highest is the courage to express personal feelings. There 8 types in interpersonal: easy to socialize, helpful, emphaty, tolerance, concern with the environment, harmonious, democratic, paying attention to others, and ability to resolve the conflict. The lowest ability is emphaty or effort to understand the others, while the highest is acting democratically, ability to resolve the conflicts, and to pay attention to the others